Use and abuse of antidumping by global cartels - Arevik Gnutzmann-Mkrtchyan; Martin Hoffstadt (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
Antidumping creates opportunities for abuse to stifle market competition. Whether cartels actually abuse trade policy for anticompetitive purposes remains an open question in the literature. To address this gap, we construct a novel dataset that matches cartel investigations with trade data at the product level. We then estimate the world import price and quantity effects of antidumping in cartel products. We find that the use of antidumping in cartel industries helps to maintain higher world import prices and lower quantities during cartel periods, and to induce the establishment of a cartel. The effect is present both for antidumping cases that result in duties and cases that are withdrawn by the petitioning industry.
Keywords: F14; F15; L41; 330